Effect of culture system on the prevalence of parasites of the Mediterranean mussel Mytilus galloprovincialis (Lamark, 1819) - KARAGIANNIS (Δ. ΚΑΡΑΓΙΑΝΝΗΣ) D.; VATSOS (Ι.Ν. ΒΑΤΣΟΣ) I. N.; THEODORIDIS (Α. ΘΕΟΔΩΡΙΔΗΣ) A.; ANGELIDIS (Π. ΑΓΓΕΛΙΔΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
For the production of the Mediterranean mussel, Mytilus galloprovincialis, two systems are used in Greece, the ‘long-line’ and the ‘on-table’ system. In the present study, effects of farming system on prevalence of infection by some parasites of Mediterranean mussels were investigated. Three mussel culture sites, located at Thermaikos gulf, with similar profiles, where both farming systems are practiced, were selected. Two samplings took place in 2008, one in July and one in October. From each site, 30 mussels per culture system were collected. From each mussel, tissue samples from the visceral mass, mantle and gills were collected and examined histologically for the presence of any parasites. Number of mussels parasitized by at least one parasitic species was substantially increased in mussels cultured with the ‘on-table’ system. In particular, prevalence of infection by Urastoma cyprinae and Marteilia spp. was substantially increased in mussels cultured with the ‘on-table’ system, while no relation between farming system and prevalence of infection by Eugymnanthea inquilina was observed. Prevalence of infection by Myticola intestinalis, Steinhausia mytilovum and Proctoeces maculatus was considerably low in both culture systems. In addition, in both culture systems, number of the mussels infected by E. inquilina and U. cyprinae was substantially increased in October, while an opposite trend was noted for Marteilia spp.